PERSEPSI WISATAWAN TERHADAP SARANA PRASANA PENDUKUNG DESTINASI WISATA BUKIT PORONG, DESA WISATA COAL - Gregorius Berybe; Linda Marlince Taka; Fresnawati Missa Mensi (Pusat Penelitian dan Pengabdian Politeknik eLBajo Commodus, 2022)
Tourism villages present in the tourism system in supporting the concept of community-based tourism. One of the new tourist villages in West Manggarai is Coal Bu Porong Village, which was built on the creativity of porong hill youth. The purpose of this study is to find out the facilities and infrastructure available in Bukit Porong and to find out the perceptions of visitors about the facilities and infrastructure supporting the Bukit Porong tourist village. This study uses a qualitative approach to determine the variables of facilities and infrastructure such as objects, access, accommodation, facilities, transportation, food and drink services, recreational activities, shopping, communication, banking system, health, security, hygiene, worship facilities. The data collected was obtained from interviews, observations and documentation, where the number of respondents were 20 people consisting of pokdarwis groups, communities, village heads, visitors, tourism offices. The results of this study show that the facilities and infrastructure available in Bukit Porong such as natural attractions, artificial attractions, cultural attractions, homestays, access, information officers, local snacks of Bukit Porong, various recreational activities, places of purchase, communication facilities, cleaning facilities that are considered quite adequate because they are suppoerted by local communities, variables of facilities and infrastructure such as natural attractions and facilities Communication has met the perceptions or criteria of visitors, but still found the criteria of Objects (cultural, artificial), Access, Accommodation, Transportation, Food and beverage services, Recreational activities, shopping, communication, health, security, hygiene, worship facilities, sports facilities and educational facilities that are still considered lack of attention by visitors so that further handling is needed by porong hill managers to tourists' perceptions of facilities and infrastructure. Keywords: Perception, Tourism villages, facilities and infrastructure